Political innovation, digitalisation and public participation in party politics. (1st July 2019) - Schmidthuber, Lisa; Hilgers, Dennis; Rapp, Maximilian
Abstract : Citizen engagement is seen as a way to address a range of societal challenges, fiscal constraints, as well as wicked problems, and increasing public participation in political decisions could help to address low levels of trust in politicians and decreasing satisfaction with political parties. This paper examines the perceived impacts of an experiment by the Austrian People's Party which, in response to reaching a historic low in the polls, opened up its manifesto process to public participation via digital technology. Analysis of survey data from participants found that self-efficacy is positively associated with participation intensity but negatively related to satisfaction. In contrast, collective efficacy is related to positive perceptions of public participation in party politics but does not influence levels of individual participation. Future research is needed to explore the outcomes of political innovations that use digital technologies to enable public participation on voting behaviour, party membership and attitudes to representative democracy.